Pharmacokinetic/pharmacodynamic evaluation of linezolid in hospitalized paediatric patients: a step toward dose optimization by means of therapeutic drug monitoring and Monte Carlo simulation. - Cojutti, Piergiorgio; Maximova, Natalia; Crichiutti, Giovanni; Isola, Miriam; Pea, Federico (J Antimicrob Chemother, 2015)
OBJECTIVES: To report on linezolid exposure in a paediatric population who routinely underwent therapeutic drug monitoring (TDM) for dosage optimization and to assess the factors affecting interpatient variability. METHODS: We performed a retrospective study of patients whose plasma C(min) and Cmax levels were measured during linezolid treatment. Adequate exposure was defined as a C(min) of 2-7 mg/L and/or an estimated AUC24 of 160-300 mg · h/L. Patients were divided into two subgroups (Group 1, 2-11 years; Group 2, 12-18 years). Monte Carlo simulation was performed to investigate whether or not the currently recommended dosages might enable a high probability of target attainment (PTA) of two thresholds for linezolid efficacy (AUC24/MIC ≥ 80 or ≥ 100). Data on demographic characteristics, disease, microbiology and haematochemical parameters and outcomes were collected. RESULTS: A total of 23 patients were included. Standard dosages were suboptimal in 50.0% and 44.4% of patients in Group 1 and Group 2, respectively. Among those who underwent multiple instances of TDM, the dosages were increased in 33.3% of cases in both groups, and decreased in 6.6% and 9.5% of cases in Group 1 and Group 2, respectively. Co-treatment with phenobarbital, proton pump inhibitors and amiodarone accounted for most of the variability in C(min) (adjusted R(2) of 0.692). Simulations showed a PTA of ≥ 90% with the current dosing regimens in both groups only for pathogens with an MIC ≤ 1 mg/L. CONCLUSIONS: Higher dosages of linezolid may be needed, especially in Group 1 when in the presence of pathogens with an MIC >1 mg/L. The role of TDM should be encouraged for optimization of linezolid exposure in the paediatric setting in the presence of infections caused by pathogens with borderline susceptibility and/or for patients co-treated with drugs that may alter linezolid exposure.
Keywords: Acetamides; Anti-Bacterial Agents; Area Under Curve; Child; Child, Preschool; Drug Monitoring; Female; Gram-Positive Bacterial Infections; Hospitalization; Humans; Infant; Inpatients; Linezolid; Male; Monte Carlo Method; Oxazolidinones; Plasma; Retrospective Studies; Tertiary Care Centers

Pharmacokinetics and pharmacodynamics of continuous-infusion meropenem in pediatric hematopoietic stem cell transplant patients. - Cojutti, Piergiorgio; Maximova, Natalia; Pea, Federico (Antimicrob Agents Chemother, 2015)
This study explored the pharmacokinetics and the pharmacodynamics of continuous-infusion meropenem in a population of pediatric hematopoietic stem cell transplant (HSCT) patients who underwent therapeutic drug monitoring. The relationship between meropenem clearance (CLM) and estimated creatinine clearance (CLCR) was assessed by nonlinear regression. A Monte Carlo simulation was performed to investigate the predictive performance of five dosing regimens (15 to 90 mg/kg of body weight/day) for the empirical treatment of severe Gram-negative-related infections in relation to four different categories of renal function. The optimal target was defined as a probability of target attainment (PTA) of ≥90% at steady-state concentration-to-MIC ratios (C SS/MIC) of ≥1 and ≥4 for MICs of up to 8 mg/liter. A total of 21 patients with 44 meropenem C SS were included. A good relationship between CLM and estimated CLCR was observed (r (2) = 0.733). Simulations showed that at an MIC of 2 mg/liter, the administration of continuous-infusion meropenem at doses of 15, 30, 45, and 60 mg/kg/day may achieve a PTA of ≥90% at a C SS/MIC ratio of ≥4 in the CLCR categories of 40 to <80, 80 to <120, 120 to <200, and 200 to <300 ml/min/1.73 m(2), respectively. At an MIC of 8 mg/liter, doses of up to 90 mg/kg/day by continuous infusion may achieve optimal PTA only in the CLCR categories of 40 to <80 and 80 to <120 ml/min/1.73 m(2). Continuous-infusion meropenem at dosages up to 90 mg/kg/day might be effective for optimal treatment of severe Gram-negative-related infections in pediatric HSCT patients, even when caused by carbapenem-resistant pathogens with an MIC of up to 8 mg/liter.